Insights From Long-term Follow-up of a Girl With Adrenal Insufficiency and Sphingosine-1-Phosphate Lyase Deficiency - GÜRAN, TÜLAY (My University, 2022)
Introduction: Sphingosine-1-phosphate lyase (SGPL1) insuffciency syndrome (SPLIS) is a multisystemic disorder which, in the main, incorporates steroid-resistant nephrotic syndrome and primary adrenal insuffciency (PAI). Case Presentation: We present a young girl with a novel homozygous variant in SGPL1, p.D350G, with PAI in the absence of nephrotic syndrome. In the course of 15 years of follow-up she has further developed primary hypothyroidism and while she has progressed through puberty appropriately, ovarian calcifcations were noted on imaging. The p.D350G variant results in reduced protein expression of SGPL1. We demonstrate that CRISPR engineered knockout of SGPL1 in human adrenocortical (H295R) cells abrogates cortisol production. Furthermore, while wild-type SGPL1 is able to rescue cortisol production in this in vitro model of adrenal disease, this is not observed with the p.D350G mutant. Conclusion: SGPL1 defciency should be considered in the differential diagnosis of PAI with close attention paid to evolving disease on follow-up. Key Words: SGPL1, sphingolipids, adrenal insuffciency, steroidogenesis, ovarian calcifcation
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endocrinology; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Life Sciences; SGPL1; sphingolipids; adrenal insufficiency; steroidogenesis; ovarian calcification; STABILITY CHANGES; PROTEIN STABILITY; MUTATIONS; SERVER; SEQUENCE